KOMUNIKASI PENYULUH PERTANIAN DALAM PEMBANGUNAN PERTANIAN DI KELURAHAN BONGKI, KECAMATAN SINJAI UTARA, KABUPATEN SINJAI - Anna, Anna; Astaman, Putra; Nurdin, Fadillah (Lembaga Penelitian, Pengembangan, Pemberdayaan Potensi Indonesia, 2025)
The purpose of this study was to understand how agricultural extension communication contributed to the advancement of the agricultural sector in Bongki Village, North Sinjai District, Sinjai Regency. This study used a qualitative descriptive approach with purposive sampling, involving a total of 25 participants, including one agricultural extension officer and 24 farmers who were members of a farmer group. Data collection was conducted through interviews, observations, and documentation, which were then analyzed through data reduction, data presentation, and conclusion drawing using triangulation techniques to improve the accuracy of the results. The findings of this study indicate that communication from agricultural extension workers plays an important role in improving farmers' knowledge, attitudes, and skills. Extension workers act as communicators, facilitators, motivators, and mentors who are able to create interactive relationships with farmers. Extension activities encourage changes in farmers' mindsets and behaviors, which in turn increase productivity and strengthen sustainable farm management. This study concludes that the success of development in Bongki Village is highly dependent on the effectiveness of responsive and sustainable extension communication, which is able to adapt methods to the situations faced by farmers.